Cable interface bonding modified material and preparation method thereof

By combining modified materials with a specific proportion of matrix resin, modifier and conductive filler in the cable interface, the problem of unstable bonding of the semiconductor shield layer and the insulating layer interface is solved, and the interface bonding strength and temperature resistance cycle are improved Performance ensures the stability and conductivity of the cable.

CN119241951AActive Publication Date: 2025-01-03ANGREEN DONGGUAN NEW MATERIALS TECH

Patent Information

Application Number
CN202411611455.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-03
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The interface of the semiconducting shielding layer and the insulating layer in existing cables is unstable, resulting in the cable's reliability affected by thermal expansion and contraction during operation.

Method used

The cable interface of the cable interface using 50-60% matrix resin, 15-20% modifier and 25-30% conductive filler is combined with the modified material, and the introduction of a specific proportion of elastomer and hyperbranched polyester into the matrix resin is carried out. Functional group modifiers form a stable interface structure and enhance interface binding stability.

Benefits of technology

The interface combination strength and temperature cycling resistance are significantly improved, ensuring the stability and conductivity of the cable under temperature changes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a cable interface bonding modified material and a preparation method thereof, and the cable interface bonding modified material comprises the following components in percentage by mass: 50-60% of matrix resin, 15-20% of a modifier and 25-30% of a conductive filler, wherein the matrix resin is composed of polypropylene and an elastomer, and the mass ratio of the polypropylene to the elastomer is (2.2-2.8): 1; the modifier is a hyperbranched polyester polyfunctional group modifier, the molecular weight of the hyperbranched polyester polyfunctional group modifier is 9000-11000, and the density of polar groups in the hyperbranched polyester polyfunctional group modifier is 2.5-3.5 mmol / g. According to the technical scheme, the interface bonding stability of the semi-conductive shielding layer and the insulating layer of the cable can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable materials, and in particular to a cable interface bonding modified material and a preparation method thereof. Background Art

[0002] High-voltage DC cables are important carriers of energy transmission, and their structures mainly include conductors, inner semi-conductive shielding layers, insulating layers, outer semi-conductive shielding layers, etc. Among them, the insulating layer is the core component of the cable and plays the role of electrical insulation; the semi-conductive shielding layer is located between the conductor and the insulating layer, and is mainly used to even out the electric field distribution on the conductor surface, regulate the electric field transition between the conductor and the insulating layer, and prevent the accumulation of space charge in the insulating layer.

[0003] At present, the semi-conductive shielding layer in the cable is usually made of a polymer composite material with conductive fillers added. The introduction of conductive fillers makes the semi-conductive shielding layer have strong polarity, while the insulating layer mainly uses non-polar polyolefin materials. Due to the significant differences in molecular structure and polarity between the two materials, their interface compatibility is poor, and microscopic defects are easily formed at the interface, resulting in unstable interface bonding between the semi-conductive shielding layer and the insulating layer. Especially during the operation of the cable, the Joule heat generated by the conductor when it is energized will cause the material to expand and contract. This temperature cycle further aggravates the problem of unstable interface bonding and affects the operating reliability of the cable. Summary of the invention

[0004] The main purpose of the invention is to solve the technical problem of unstable interface bonding between the semi-conductive shielding layer and the insulating layer of the existing cable.

[0005] The first aspect of the present invention provides a cable interface bonding modified material, which comprises, by mass percentage, 50-60% of a base resin, 15-20% of a modifier, and 25-30% of a conductive filler; wherein the base resin is composed of polypropylene and an elastomer, and the mass ratio of the polypropylene to the elastomer is (2.2-2.8):1; the modifier is a hyperbranched polyester multifunctional modifier, the molecular weight of the hyperbranched polyester multifunctional modifier is 9000-11000, and the density of polar groups in the hyperbranched polyester multifunctional modifier is 2.5-3.5mmol / g.

[0006] Optionally, the elastomer is a styrene-ethylene-butylene-styrene block copolymer, the styrene content of the styrene-ethylene-butylene-styrene block copolymer is 28-32wt%, and the melt index of the styrene-ethylene-butylene-styrene block copolymer is 3.5-4.5g / 10min; the polypropylene is an isotactic polypropylene with a tacticity greater than 95%, and the melt index of the isotactic polypropylene is 1.5-2.5g / 10min.

[0007] Optionally, the conductive filler is carbon nanoparticles, the particle size of the carbon nanoparticles is 25-45nm, and the specific surface area of ​​the carbon nanoparticles is 600-900m² / g; the surface of the carbon nanoparticles is carboxylated, the carboxyl content of the surface of the carbon nanoparticles is 2.5-3.5mmol / g, and the surface of the carbon nanoparticles also contains 0.8-1.2mmol / g of hydroxyl groups.

[0008] Optionally, the cable interface bonding modification material further comprises 1.5-2.5wt% of a silane-epoxy bifunctional coupling agent, wherein the silane-epoxy bifunctional coupling agent comprises a silane group and an epoxy group, and a molar ratio of the silane group to the epoxy group is 1:(1.3-1.4).

[0009] Optionally, the hyperbranched polyester multifunctional modifier has 12-15 terminal hydroxyl groups, the hydroxyl value of the hyperbranched polyester multifunctional modifier is 95-115 mgKOH / g, and the branching degree of the hyperbranched polyester multifunctional modifier is 0.38-0.42; 55-65% of the terminal hydroxyl groups undergo esterification reaction with maleic anhydride to form ester groups, and 80-90% of the remaining unreacted terminal hydroxyl groups undergo ring-opening reaction with the epoxy groups in the silane epoxy bifunctional coupling agent.

[0010] Optionally, the cable interface bonding modification material also includes 0.3-0.8wt% of an antioxidant, the antioxidant includes a hindered phenol antioxidant and a sulfur-based synergist, and the mass ratio of the hindered phenol antioxidant to the sulfur-based synergist is (1.4-1.6):1; the hindered phenol antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and the sulfur-based synergist is dioctadecyl thiodipropionate.

[0011] The second aspect of the present invention provides a method for preparing a cable interface bonding modified material, comprising the following steps: The first step is to weigh 100 parts of raw materials in total, including 18-22 parts of elastomer, 15-20 parts of hyperbranched polyester multifunctional modifier, 45-53 parts of polypropylene, 25-30 parts of carbon nanoparticles, 1.5-2.5 parts of silane epoxy bifunctional coupling agent, and 0.3-0.8 parts of antioxidant; The second step is to add the carbon nanoparticles into xylene, control the mass ratio to be 1:(4-5), and ultrasonically disperse for 30-40 minutes to obtain a carbon nanoparticle dispersion; The third step is to dissolve the elastomer in the carbon nanoparticle dispersion, and stir and dissolve at 80-90° C. to obtain an elastomer solution; Step 4: Mix the hyperbranched polyester multifunctional modifier and maleic anhydride in a molar ratio of 1:(0.6-0.7), add to the elastomer solution, heat to 115-125° C., stir and react for 1-2 hours; add the polypropylene, and continue stirring and reacting for 0.5-1 hour; Step 5: Cooling the mixture to 90-100° C., dissolving the silane-epoxy bifunctional coupling agent in isopropanol, controlling the mass fraction to be 3-5%, and slowly adding the mixture obtained in step 4; Step 6, removing the solvent by vacuum distillation, controlling the temperature to 85-95° C., to obtain a primary product; Step 7: melt-kneading the primary product in a co-rotating twin-screw extruder at an extrusion temperature of 165-175° C. and a screw speed of 300-500 r / min; In the eighth step, the extruded product is vacuum dried at 70-80° C. for 4-6 hours to obtain a cable interface bonding modified material.

[0012] Optionally, in the fifth step, the temperature of the mixture obtained in the fourth step is controlled to be 85-90°C; the addition rate of the silane epoxy bifunctional coupling agent solution is 2-4 ml / min; after the addition is completed, the temperature is raised to 95-100°C at a rate of 2-3°C / min, and the reaction is kept warm for 0.5-1h.

[0013] Optionally, before the sixth step, an antioxidant is added to the product after the fifth step reaction is completed, and the amount of the antioxidant added is 0.3-0.8wt% of the total mass of the product; the antioxidant consists of a hindered phenol antioxidant and a sulfur-based synergist, and the mass ratio of the hindered phenol antioxidant to the sulfur-based synergist is (1.4-1.6):1; the pressure of the reduced pressure distillation is 30-40kPa, and the distillation time is 2-3h.

[0014] The present invention provides a cable interface bonding modified material, which improves the elastic deformation capacity of the base material and enhances its adaptability to temperature cycles by introducing a specific proportion of elastomer into the base resin (the mass ratio of polypropylene to elastomer is (2.2-2.8):1). At the same time, a hyperbranched polyester multifunctional modifier and a conductive filler are used to synergize, on the one hand, chemical bonding is formed by the polar groups in the modifier molecules and the functional groups on the surface of the conductive filler, and on the other hand, the terminal hydroxyl groups react with the base resin, so that a stable interface structure is formed between the semi-conductive shielding layer and the insulating layer, and the interface bonding stability between the two layers is effectively improved. DETAILED DESCRIPTION

[0015] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0016] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0017] The raw materials and their sources used in the examples of the present invention are as follows: The elastomer uses commercially available styrene-ethylene-butylene-styrene block copolymer (SEBS), purchased from Asahi Kasei Corporation of Japan, with a styrene content of 30wt% and a melt index of 4.0g / 10min (230℃, 2.16kg); polypropylene (PP) uses isotactic polypropylene with a tacticity greater than 95%, purchased from Sinopec Corporation, with a melt index of 2.0g / 10min (230℃, 2.16kg); carbon nanoparticles use conductive carbon black with an average particle size of 35nm, purchased from Immer, Germany Reese Company, with a specific surface area of ​​750m² / g; the hyperbranched polyester multifunctional modifier is a hyperbranched polyester with a hydroxyl value of 105mgKOH / g, purchased from American Standard Company, with a molecular weight of 10000; the silane epoxy bifunctional coupling agent is γ-glycidyloxypropyltrimethoxysilane, purchased from Dow Corning Company, USA; the antioxidant is a hindered phenol antioxidant tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester and a sulfur-based synergist dioctadecyl thiodipropionate, both purchased from BASF, Germany.

[0018] Before the preparation of the examples, the raw materials need to be pretreated. Polypropylene and SEBS are placed in a vacuum drying oven, the temperature is controlled to 80±2°C, and the drying time is 12 hours to remove moisture and volatile substances in the materials. The carbon nanoparticles are dried in a vacuum drying oven at 70±2°C for 8 hours to improve their dispersibility. Other raw materials must be sealed and stored in a desiccator before use to avoid moisture.

[0019] The main equipment used in the preparation process includes: 1. Vacuum drying oven: temperature control range 20-200℃, control accuracy ±1℃; 2. Closed rotor mixer: operating temperature range 50-200℃, rotor speed 0-100rpm; 3. Co-rotating twin-screw extruder: screw diameter 40mm, aspect ratio 40:1, temperature control range 50-300℃; 4. Vacuum oven: temperature control range 20-200℃, vacuum degree ≤133Pa.

[0020] Example 1 The cable interface bonding modified material was prepared as follows: In the first step, weigh the following raw materials by mass percentage: 55% base resin (of which the mass ratio of polypropylene to SEBS is 2.5:1), 17% hyperbranched polyester multifunctional modifier, 27% carbon nanoparticles, 2.0% silane epoxy bifunctional coupling agent, 0.5% antioxidant (of which the mass ratio of hindered phenol antioxidant to sulfur-based synergist is 1.5:1).

[0021] In the second step, the carbon nanoparticles were added to xylene, the mass ratio was controlled to be 1:4.5, and ultrasonic dispersion was performed for 35 minutes to obtain a carbon nanoparticle dispersion; The third step is to dissolve SEBS in the carbon nanoparticle dispersion and stir and dissolve at 85° C. to obtain a uniform elastomer solution; Step 4: Mix the hyperbranched polyester multifunctional modifier and maleic anhydride at a molar ratio of 1:0.65, add to the elastomer solution, heat to 120° C., and stir to react for 1.5 hours; add polypropylene, and continue stirring to react for 0.8 hours; Step 5: Cool down to 95°C, dissolve the silane epoxy bifunctional coupling agent in isopropanol, control the mass fraction to be 4%, and slowly add it to the mixture obtained in step 4 at a rate of 3 ml / min; after the addition is completed, heat up to 98°C at a rate of 2.5°C / min, and keep the reaction for 0.8h; Step 6: Add antioxidant and remove the solvent by vacuum distillation, control the temperature to 90°C, the pressure to 35 kPa, and the distillation time to 2.5 h; Step 7: melt-kneading the obtained product in a co-rotating twin-screw extruder at an extrusion temperature of 170° C. and a screw speed of 400 r / min; In the eighth step, the extruded product is vacuum dried at 75° C. for 5 h to obtain a cable interface bonding modified material.

[0022] Example 2 The cable interface bonding modified material was prepared as follows: In the first step, the following raw materials were weighed in percentage by mass: 52% base resin (the mass ratio of polypropylene to SEBS was 2.3:1), 19% hyperbranched polyester multifunctional modifier, 28% carbon nanoparticles, 1.8% silane epoxy bifunctional coupling agent, and 0.6% antioxidant (the mass ratio of hindered phenol antioxidant to sulfur-based synergist was 1.5:1).

[0023] In the second step, the carbon nanoparticles were added to xylene, the mass ratio was controlled to be 1:4.5, and ultrasonic dispersion was performed for 35 minutes to obtain a carbon nanoparticle dispersion; The third step is to dissolve SEBS in the carbon nanoparticle dispersion and stir and dissolve at 85° C. to obtain a uniform elastomer solution; Step 4: Mix the hyperbranched polyester multifunctional modifier and maleic anhydride at a molar ratio of 1:0.65, add to the elastomer solution, heat to 120° C., and stir to react for 1.5 hours; add polypropylene, and continue stirring to react for 0.8 hours; Step 5: Cool down to 95°C, dissolve the silane epoxy bifunctional coupling agent in isopropanol, control the mass fraction to be 4%, and slowly add it to the mixture obtained in step 4 at a rate of 3 ml / min; after the addition is completed, heat up to 98°C at a rate of 2.5°C / min, and keep the reaction for 0.8h; Step 6: Add antioxidant and remove the solvent by vacuum distillation, control the temperature to 90°C, the pressure to 35 kPa, and the distillation time to 2.5 h; Step 7: melt-kneading the obtained product in a co-rotating twin-screw extruder at an extrusion temperature of 170° C. and a screw speed of 400 r / min; In the eighth step, the extruded product is vacuum dried at 75° C. for 5 h to obtain a cable interface bonding modified material.

[0024] Example 3 The cable interface bonding modified material was prepared as follows: In the first step, the following raw materials were weighed in percentage by mass: 58% base resin (the mass ratio of polypropylene to SEBS was 2.7:1), 15% hyperbranched polyester multifunctional modifier, 25% carbon nanoparticles, 2.2% silane epoxy bifunctional coupling agent, and 0.4% antioxidant (the mass ratio of hindered phenol antioxidant to sulfur-based synergist was 1.5:1).

[0025] In the second step, the carbon nanoparticles were added to xylene, the mass ratio was controlled to be 1:4.5, and ultrasonic dispersion was performed for 35 minutes to obtain a carbon nanoparticle dispersion; The third step is to dissolve SEBS in the carbon nanoparticle dispersion and stir and dissolve at 85° C. to obtain a uniform elastomer solution; Step 4: Mix the hyperbranched polyester multifunctional modifier and maleic anhydride at a molar ratio of 1:0.65, add to the elastomer solution, heat to 120° C., and stir to react for 1.5 hours; add polypropylene, and continue stirring to react for 0.8 hours; Step 5: Cool down to 95°C, dissolve the silane epoxy bifunctional coupling agent in isopropanol, control the mass fraction to be 4%, and slowly add it to the mixture obtained in step 4 at a rate of 3 ml / min; after the addition is completed, heat up to 98°C at a rate of 2.5°C / min, and keep the reaction for 0.8h; Step 6: Add antioxidant and remove the solvent by vacuum distillation, control the temperature to 90°C, the pressure to 35 kPa, and the distillation time to 2.5 h; Step 7: melt-kneading the obtained product in a co-rotating twin-screw extruder at an extrusion temperature of 170° C. and a screw speed of 400 r / min; In the eighth step, the extruded product is vacuum dried at 75° C. for 5 h to obtain a cable interface bonding modified material.

[0026] Comparative Example 1 In order to verify the excellent performance of the modified material of the present invention, comparative example 1 was designed, and its preparation steps were the same as those of example 1, but no hyperbranched polyester multifunctional modifier was added, and the specific formula was as follows: In the first step, the following raw materials were weighed in percentage by mass: 72% base resin (wherein the mass ratio of polypropylene to SEBS was 2.5:1), 27% carbon nanoparticles, 2.0% silane epoxy bifunctional coupling agent, and 0.5% antioxidant (wherein the mass ratio of hindered phenol antioxidant to sulfur-based synergist was 1.5:1).

[0027] The subsequent preparation steps are the same as those in Example 1.

[0028] Comparative Example 2 Comparative Example 2 does not add SEBS, and the specific proportions are as follows: In the first step, the following raw materials are weighed in percentage by mass: 55% polypropylene, 17% hyperbranched polyester multifunctional modifier, 27% carbon nanoparticles, 2.0% silane epoxy bifunctional coupling agent, and 0.5% antioxidant (the mass ratio of hindered phenol antioxidant to sulfur-based synergist is 1.5:1).

[0029] The subsequent preparation steps are the same as those in Example 1.

[0030] Comparative Example 3 Comparative Example 3 does not add a silane-epoxy bifunctional coupling agent, and the specific formula is as follows: In the first step, the following raw materials are weighed in percentage by mass: 57% base resin (the mass ratio of polypropylene to SEBS is 2.5:1), 17% hyperbranched polyester multifunctional modifier, 25% carbon nanoparticles, and 0.5% antioxidant (the mass ratio of hindered phenol antioxidant to sulfur-based synergist is 1.5:1).

[0031] The subsequent preparation steps are the same as those in Example 1, except that the fifth step is omitted.

[0032] Performance Testing 1. Interface bonding strength test (1) Sample preparation: The prepared modified material and polyethylene insulating material (density 0.92 g / cm³, melt index 2.0 g / 10 min) were hot pressed at 180°C and 5 MPa to form a three-layer structure sample with the structure of modified material (0.5 mm) / insulating material (1.0 mm) / modified material (0.5 mm); (2) Test conditions: room temperature (23°C), tensile rate 50 mm / min; (3) Take 5 parallel samples for testing and take the average value.

[0033] 2. Temperature resistance cycle performance test (1) Temperature cycling conditions: 23°C to 90°C cycles, 12 hours per cycle, 100 cycles in total; (2) After cycling, test according to the above-mentioned interface bonding strength test method; (3) Strength retention rate = strength after cycle / initial strength × 100%.

[0034] 3. Volume resistivity test (1) Sample preparation: The material was prepared into a disc sample with a thickness of 2 mm; (2) Test conditions: Tested at 23°C and 90°C using the four-probe method; (3) Test each temperature point three times and take the average value.

[0035] 4. Microscopic morphology analysis (1) The material is brittle fractured in liquid nitrogen to obtain the cross section; (2) The cross-sectional morphology was observed using a scanning electron microscope with an accelerating voltage of 15 kV; (3) Focus on analyzing the interface bonding and the dispersion state of the conductive filler.

[0036] Test Results Table 1 Performance test results of various embodiments and comparative examples Sample No. Interface bonding strength (MPa) Strength retention after temperature cycling (%) 23℃ Volume resistivity (Ω·cm) 90℃ Volume resistivity (Ω·cm) Example 1 3.2 92 75 280 Example 2 3.5 90 82 295 Example 3 3.0 88 68 265 Comparative Example 1 1.8 65 95 340 Comparative Example 2 1.5 55 88 325 Comparative Example 3 2.0 70 85 315 From the test results we can see that: 1. Interface bonding performance: The interface bonding strengths of Examples 1-3 all exceed 3.0 MPa, which is significantly better than Comparative Examples 1-3 (all below 2.0 MPa). This indicates that the ternary compound system provided by the present invention can effectively improve the interface bonding performance of the material.

[0037] 2. Temperature cycle resistance: The strength retention rates of Examples 1-3 after 100 temperature cycles were all above 88%, while the strength retention rates of Comparative Examples 1-3 were all below 70%, which indicates that the material system of the present invention has excellent interface bonding stability.

[0038] 3. Conductive properties: The volume resistivity of all samples at 23°C and 90°C meets the actual use requirements, but the resistivity increase of Examples 1-3 at high temperature is relatively small, indicating that its conductive network structure is more stable. This is due to the introduction of the modifier to improve the dispersion state of the conductive filler.

[0039] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A cable interface bonding modified material, characterized in that: In terms of mass percentage, the cable interface bonding modification material comprises: 50-60% of a base resin, 15-20% of a modifier, and 25-30% of a conductive filler; wherein the base resin is composed of polypropylene and an elastomer, and the mass ratio of the polypropylene to the elastomer is (2.2-2.8):1; the modifier is a hyperbranched polyester multifunctional modifier, the molecular weight of the hyperbranched polyester multifunctional modifier is 9000-11000, and the density of polar groups in the hyperbranched polyester multifunctional modifier is 2.5-3.5mmol / g.

2. The cable interface bonding modified material according to claim 1, characterized in that: The elastomer is a styrene-ethylene-butylene-styrene block copolymer, the styrene content of the styrene-ethylene-butylene-styrene block copolymer is 28-32wt%, and the melt index of the styrene-ethylene-butylene-styrene block copolymer is 3.5-4.5g / 10min; the polypropylene is an isotactic polypropylene with a tacticity greater than 95%, and the melt index of the isotactic polypropylene is 1.5-2.5g / 10min.

3. The cable interface bonding modified material according to claim 1, characterized in that: The conductive filler is carbon nanoparticles, the particle size of the carbon nanoparticles is 25-45nm, and the specific surface area of ​​the carbon nanoparticles is 600-900m² / g; the surface of the carbon nanoparticles is carboxylated, the carboxyl content of the surface of the carbon nanoparticles is 2.5-3.5mmol / g, and the surface of the carbon nanoparticles also contains 0.8-1.2mmol / g of hydroxyl groups.

4. The cable interface bonding modified material according to claim 3, characterized in that: The cable interface bonding modification material also includes 1.5-2.5wt% of a silane-epoxy bifunctional coupling agent, wherein the silane-epoxy bifunctional coupling agent includes a silane group and an epoxy group, and the molar ratio of the silane group to the epoxy group is 1:(1.3-1.4).

5. The cable interface bonding modified material according to claim 4, characterized in that: The hyperbranched polyester multifunctional modifier has 12-15 terminal hydroxyl groups, the hydroxyl value of the hyperbranched polyester multifunctional modifier is 95-115 mgKOH / g, and the branching degree of the hyperbranched polyester multifunctional modifier is 0.38-0.42; 55-65% of the terminal hydroxyl groups undergo esterification reaction with maleic anhydride to form ester groups, and 80-90% of the remaining unreacted terminal hydroxyl groups undergo ring-opening reaction with the epoxy groups in the silane epoxy bifunctional coupling agent.

6. The cable interface bonding modified material according to claim 4, characterized in that: The cable interface bonding modified material also includes 0.3-0.8wt% of an antioxidant, the antioxidant includes a hindered phenol antioxidant and a sulfur-based synergist, and the mass ratio of the hindered phenol antioxidant to the sulfur-based synergist is (1.4-1.6):1; the hindered phenol antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and the sulfur-based synergist is dioctadecyl thiodipropionate.

7. A method for preparing a cable interface bonding modified material, used for preparing the cable interface bonding modified material as claimed in any one of claims 1 to 6, characterized in that: The steps include: The first step is to weigh 100 parts of raw materials in total, including 18-22 parts of elastomer, 15-20 parts of hyperbranched polyester multifunctional modifier, 45-53 parts of polypropylene, 25-30 parts of carbon nanoparticles, 1.5-2.5 parts of silane epoxy bifunctional coupling agent, and 0.3-0.8 parts of antioxidant; The second step is to add the carbon nanoparticles into xylene, control the mass ratio to be 1:(4-5), and ultrasonically disperse for 30-40 minutes to obtain a carbon nanoparticle dispersion; The third step is to dissolve the elastomer in the carbon nanoparticle dispersion, and stir and dissolve at 80-90° C. to obtain an elastomer solution; Step 4: Mix the hyperbranched polyester multifunctional modifier and maleic anhydride in a molar ratio of 1:(0.6-0.7), add to the elastomer solution, heat to 115-125° C., stir and react for 1-2 hours; add the polypropylene, and continue stirring and reacting for 0.5-1 hour; Step 5: Cooling the mixture to 90-100° C., dissolving the silane-epoxy bifunctional coupling agent in isopropanol, controlling the mass fraction to be 3-5%, and slowly adding the mixture obtained in step 4; Step 6, removing the solvent by vacuum distillation, controlling the temperature to 85-95° C., to obtain a primary product; Step 7: melt-kneading the primary product in a co-rotating twin-screw extruder at an extrusion temperature of 165-175° C. and a screw speed of 300-500 r / min; In the eighth step, the extruded product is vacuum dried at 70-80° C. for 4-6 hours to obtain a cable interface bonding modified material.

8. The method for preparing the cable interface bonding modified material according to claim 7, characterized in that: In the fifth step, the temperature of the mixture obtained in the fourth step is controlled to be 85-90°C; the addition rate of the silane epoxy bifunctional coupling agent solution is 2-4 ml / min; after the addition is completed, the temperature is raised to 95-100°C at a rate of 2-3°C / min, and the reaction is kept warm for 0.5-1h.

9. The method for preparing the cable interface bonding modified material according to claim 7, characterized in that: Before the sixth step, an antioxidant is added to the product after the fifth step reaction is completed, and the added amount of the antioxidant is 0.3-0.8wt% of the total mass of the product; the antioxidant is composed of a hindered phenol antioxidant and a sulfur-based synergist, and the mass ratio of the hindered phenol antioxidant to the sulfur-based synergist is (1.4-1.6):1; the pressure of the reduced pressure distillation is 30-40kPa, and the distillation time is 2-3h.

Citation Information

Patent Citations

  • Preparation method of semiconductive shielding material for polypropylene insulation cables

    CN106009265A

  • Toughened nylon and preparation method thereof

    CN108587142A

  • Polypropylene composition and preparation method thereof

    CN114409999A

  • Polypropylene external shielding material for power cable and preparation method of polypropylene external shielding material

    CN117304604A

  • Adherent, modified thermoplastic elastomeric blends, articles, and methods

    US20050131154A1

Cited By

  • Preparation method and application of water-based high-solid novel graphene zinc heavy anti-corrosion coating

    CN120005485A

  • Preparation method and application of an aqueous high-solid graphene zinc heavy-duty anticorrosive coating

    CN120005485B

  • Polypropylene mute pipe

    CN122100632A